1998
DOI: 10.1080/11250009809386793
|View full text |Cite
|
Sign up to set email alerts
|

Allozymic variability and biogeographic relationships in twoLeuciscusspecies complexes (Cyprinidae) from southern Europe, with the rehabilitation of the genusTelestesBonaparte

Abstract: Genetic variability was assessed in eight populations belonging to the Leuciscus souffla complex and in nine populations of Leuciscus cephalus, sampled in France, Italy and Greece and in one population of Leuciscus lucumonis, endemic to Italy. Twenty-six enzymatic loci were analysed in order to clarify the genetic relationships, the patterns of colonisation of peri-Mediterranean area and the taxonomic positions. Results indicate a more ancient penetration of the Leuciscus souffia complex in southern Europe (po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
6
25
1
Order By: Relevance
“…The phylogenetic split revealed by the phylogenetic analyses supports the evolutionary bifurcation between two monophyletic lineages defined by several authors as Telestes souffia in southern France and Telestes muticellus in the Italian peninsula (Ketmaier et al, 1998;Zardoya & Doadrio, 1998, 1999Machordom et al, 1999;Stefani et al, 2004;Zaccara et al, 2007). The genetic distance for cytochrome b was over 8%, congruent with data published by Zardoya & Doadrio (1999) which estimated the divergence time between the two sister species as approximately 5 Myr: data consistent with the control (Stefani et al, 2004;Zaccara et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The phylogenetic split revealed by the phylogenetic analyses supports the evolutionary bifurcation between two monophyletic lineages defined by several authors as Telestes souffia in southern France and Telestes muticellus in the Italian peninsula (Ketmaier et al, 1998;Zardoya & Doadrio, 1998, 1999Machordom et al, 1999;Stefani et al, 2004;Zaccara et al, 2007). The genetic distance for cytochrome b was over 8%, congruent with data published by Zardoya & Doadrio (1999) which estimated the divergence time between the two sister species as approximately 5 Myr: data consistent with the control (Stefani et al, 2004;Zaccara et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…The taxonomic structure of vairone has been recently debated, and it was included in the genus Telestes (Zardoya & Doadrio, 1998, 1999Ketmaier et al, 1998;Machordom et al, 1999), even if some authors have preferred to include the species within the genus Leuciscus (Salzburger et al, 2003;Salducci et al, 2004). In this phylogeographic study, vairone has been included within the genus Telestes, and thus the Italian populations are referred to as Telestes muticellus (Bonaparte 1837) when the transalpine vairone is named Telestes souffia (or Leuciscus souffia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the natural distribution of most species in this category is the biogeographic indicator of palaeogeographic or palaeoecological events, which involved the orogenesis of mountains and the history of their valley or river drainages. For this reason, they are valuable models for phylogeographic reconstruction and molecular clock calibration (Bianco 1990;Ketmaier et al 1998Ketmaier et al , 2003Ketmaier et al , 2005Machordom & Doadrio 2001;Durand et al 2004;Doadrio & Perdices 2005).…”
Section: Salinity Tolerance and The Distribution Of Freshwater Fishesmentioning
confidence: 99%
“…This relationship is also reflected in the older taxonomy where L. souffia is called Chondrostoma rysela (Agassiz, 1835) (see also Kottelat, 1997). Thus, Ketmaier et al (1998) and Briolay et al (1998) suggested the use of the name Telestes souffia for Leuciscus souffia, already adopted in Zardoya & Doadrio (1998). Prior to any attempt to change the names of the genera more detailed studies are needed.…”
mentioning
confidence: 99%